STRUCTURAL CHANGES INDUCED BY ACTINIDES INCORPORATION IN SODA-PHOSPHATE GLASSES - SIMON, S.; ARDELEAN, I.; SIMON, V. (Studia Universitatis Babeș-Bolyai Physica, 2016)
Soda-phosphate glasses incorporating uranium and thorium were investigated with respect to structural effect of UO3 and ThO2 content added to P2O5-Na2O glass matrix, as well as to the structural effect of the self-irradiation of the actinide containing glass samples. XRD analysis proves the amorphous state of the as-prepared samples up to 20 mol %. FTIR results support the depolymerisation of the phosphate glass network by progressive increase of the amount of actinide oxide incorporated in the host glass. The self-irradiation determines the occurrence of structural defects evidenced by EPR analysis.